A Conceptual Model for Describing and Classifying Interoperability Types - Extended Abstract – CTDGSI 2025 - Santos, Kécia Souza Santana; Valle, Pedro Henrique; Maciel, Rita Suzana Pitangueira (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Interoperability is critical to modern information systems, enabling collaboration and data exchange across different software and domains. This master’s thesis reviews 37 secondary studies (2012–2023), identifying 36 types of interoperability, 117 definitions, 13 models, and six frameworks, highlighting a shift from technical to socio-technical issues. To address challenges related to this requirement fulliment, a conceptual model with two diagrams was proposed and evaluated, achieving 87.9% acceptance for the classification diagram and 78.8% for the description diagram. The research aims to improve the understanding of interoperability requirements and contribute to the challenges of the GrandSI-BR 2016–2026 roadmap.